Disparities in the Cost of Living Adjusted Earnings of Female Sex Workers in India, Thailand, and the USA: A Need to Create an Equitable Economic Survival of Female Sex Workers - Manisha N. Gore; Avinash R. Patwardhan (SAGE Publishing, 2022)
Financial necessity and desperation is the primary reason for females to enter into sex work. The health and well-being of female sex workers (FSWs) depend on the balance between their earnings and the cost of living in their local environment. Therefore it would be of value to examine the comparative cost of living adjusted earnings of FSWs in different countries to gauge equity or its absence in their financial state. Data about per client per encounter earnings for FSWs in Pune, India was taken from primary research conducted by the first author. Equivalent secondary data was acquired for the US and Thailand from an online literature review. Earnings after converting to US dollar values were adjusted against the cost of living in the respective environments of the FSWs and then compared. An FSW in India, (Pune) earned on the average US $4.40 after adjusting for the cost of living locally, while in Thailand (Bangkok) the equivalent earning was US $18.77 and in the US (Washington DC region) it was $101.79. These results suggest that an FSW in the US earns 23 times more, and a Thai FSW earns 4 times more than an FSW in India. There are numerous variables that affect the earnings of an FSW and the limited defined scope of this paper based on available data does not permit detailed analyses of causal or intermediate influencing factors. Nonetheless, it can be said with reasonable confidence that much needs to be done and can be done to mitigate the earning disparity, particularly in an emerging economy like India as shown in this small study, and that can perhaps be done best under the umbrella domain of a "harm reduction approach."